2018
DOI: 10.3329/bjch.v41i2.36103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Early Versus Delayed Enteral Feeding in Development of Necrotizing Enterocolitis for Preterm Small for Date Babies

Abstract: Abstract:Background: Growth-restricted preterm infants are at increased risk of developing necrotizing enterocolitis (NEC) group (p=0.861,p=0.881,p=0.781 respectively). Conclusion: Findings of this consecutive sampling technique concludes that early enteral feeding with breast milk does not increase the incidence of NEC, sepsis and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…Previous studies have estimated that enteral nutrition has a strong association with the incidence of NEC in about 90-95% of cases of NEC occurring in infants with initiation/reinitiation of enteral nutrition or gradual increase in nutritional volume. In contrast to the results of a study conducted by Biswas et al (2017) which compared the provision of nutrition in the two groups of early feeding versus late feeding on the risk of NEC, the results showed that the incidence of NEC was not significantly different between groups (p=1.000 vs p=0.719). In this study, the average weight of the patients in the two groups was also not significantly different (1196.3 ±135.9 grams vs. 1172.3 ±136.4 grams; p=0.288).…”
Section: Introductioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have estimated that enteral nutrition has a strong association with the incidence of NEC in about 90-95% of cases of NEC occurring in infants with initiation/reinitiation of enteral nutrition or gradual increase in nutritional volume. In contrast to the results of a study conducted by Biswas et al (2017) which compared the provision of nutrition in the two groups of early feeding versus late feeding on the risk of NEC, the results showed that the incidence of NEC was not significantly different between groups (p=1.000 vs p=0.719). In this study, the average weight of the patients in the two groups was also not significantly different (1196.3 ±135.9 grams vs. 1172.3 ±136.4 grams; p=0.288).…”
Section: Introductioncontrasting
confidence: 85%
“…In this study, the average weight of the patients in the two groups was also not significantly different (1196.3 ±135.9 grams vs. 1172.3 ±136.4 grams; p=0.288). 6 The aim of this study is to analyze the relationship between enteral and parenteral nutrition on body weight, incidence of NEC, sepsis and length of care in preterm infants at Dr Soetomo General Hospital. Dr. Soetomo General Hospital Surabaya Pharmacognosy Journal, Vol 15, Issue 1, Jan-Feb, 2023…”
Section: Introductionmentioning
confidence: 99%
“…The initiation, mode, and rate of advancement of TF remained a topic of argument [ 20 , 27 ]. Practices across NICUs and professionals are different.…”
Section: Introductionmentioning
confidence: 99%